2016
DOI: 10.1016/j.bjm.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Terpinen-4-ol, tyrosol, and β-lapachone as potential antifungals against dimorphic fungi

Abstract: This study aimed to evaluate the in vitro antifungal activity of terpinen-4-ol, tyrosol, and β-lapachone against strains of Coccidioides posadasii in filamentous phase (n = 22) and Histoplasma capsulatum in both filamentous (n = 40) and yeast phases (n = 13), using the broth dilution methods as described by the Clinical and Laboratory Standards Institute, to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of these compounds. The mechanisms of action of these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 27 publications
3
20
0
4
Order By: Relevance
“…Our results suggest that the Mesembryanthum active fraction targets the cell and nuclear membranes, as evident by the leakage of proteins and nucleic acids. These results are in agreement with those of Brilhante et al (2016) who demonstrated that tyrosol caused the leakage of protein and nucleic acids through its effect on both cellular and nuclear membrane. Their results also demonstrated the ability of tyrosol to inhibit the synthesis of ergosterol.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that the Mesembryanthum active fraction targets the cell and nuclear membranes, as evident by the leakage of proteins and nucleic acids. These results are in agreement with those of Brilhante et al (2016) who demonstrated that tyrosol caused the leakage of protein and nucleic acids through its effect on both cellular and nuclear membrane. Their results also demonstrated the ability of tyrosol to inhibit the synthesis of ergosterol.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that plant extract at a concentration of MIC/2 caused the leakage of nucleic acid (0.05) and protein (0.07) with a significant increase in absorbance higher than those obtained by control (0.01) at (260 and 280nm, respectively). These results were similar to those of Brilhante et al (2016) who reported that tyrosol caused leakage of protein and nucleic acid, emphasizing the effect of tyrosol on both cellular and nuclear membrane.…”
Section: Effect On Plasma Membrane Integritysupporting
confidence: 91%
“…), terpinen‐4‐ol, tyrosol, and β ‐lapachone (Brilhante et al . ) and novel alkylated azoles (Shrestha et al . ).…”
Section: Strategies To Combat Fungal Resistancementioning
confidence: 99%